Possibilities and challenges of social worker participation in cras: Experience report - Lorens Vasconcelos do Nascimento , Vitória; Pereira Máximo , Joelma; Fernanda Mateus da Costa , Andreza; da Silva Vieira , Reginaldo; Gonçalves Rodrigues , Jaqueline; Manoela da Silva Lima , Ana (Seven Editora, 2023)
This abstract aims to discuss the Experience Report provided through the experience of Supervised Internship I of the students of the 7th period of Social Work of FALUB, developed between August and November 2022 at the Social Assistance Reference Center - CRAS. Initially, it should be noted that the Graduation in Social Work requires internships in different socio-occupational spaces specific to the profession. Our proposal here is to highlight the importance of this insertion and contact with the professional exercise, in order to train the students in the development of a practice based on the investigative and critical dimensions, emphasizing the attributions of the social worker and the challenges faced in the professional scope. About the internship field, the CRAS is a service unit of Basic Protection of SUAS, present in the Social Assistance Policy, focusing on the promotion of the guarantee of social rights. The knowledge acquired was possible through the monitoring of the social worker as a field supervisor, developing activities to examples of follow-up in home visits, particularized care, observation of technical instruments and other attributions inherent to the profession. In this sense, it is possible to affirm through our reports that the social worker has his performance in relation to the confrontation of the expressions of the social question, in a context that evidences the social inequality, and political and cultural influences of the social classes. Thus, their professional practice is guided by their theoretical-methodological, ethical-political and technical-operative framework, which enable a critical reflection of reality and direction in commitment to the realization of social rights. Finally, we also highlight the problems posed to the profession, especially those of a managerial structural nature, which end up allowing students to reflect on the conflicts encountered and the strategies and positions specific to the direction of Social Work. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-101